Fuel blends behavior in freezing-melting phase transition - Sirviö, Katriina; Niemi, Seppo; Heikkilä, Sonja; Help, Riikka; Vauhkonen, Ville; Hiltunen, Erkki (Technische Akademie Esslingen, 2019)
Several renewable and sustainable liquid fuel alternatives are needed for different compression-ignition (CI) engine applications to reduce greenhouse gas (GHG) emissions. Biodiesels, FAMEs, have been studied for long time and apparently, despite of the problems they may have, they are still of great interest. Other options of different alternative fuels are residues and also fuels originating from circular economy. Fuel blending may be problematic, as the new mixtures may not always be miscible to each other. Due to incompatibility, such fuels can occasionally tend to be unstable when mixed. The aim of this study was to investigate if the fuels will be stable and feasible after the freezing-melting transitions. To evaluate the feasibility several storage related properties were analyzed. The mixed fuels were rapeseed methyl ester (RME) and animal-fat based methyl ester (AFME) blended with renewable naphtha and marine gas oil (MGO). Naphtha was produced from residues and MGO from used lubricants. According to the results, the freezingmelting phase transition was not a threat to the fuel quality.
Keywords: fi=Energiatekniikka|en=Energy Technology|